2020
DOI: 10.3389/fimmu.2020.00705
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Toll-Like Receptors Mediate Thromboinflammatory Responses in Patients With Essential Thrombocythemia

Abstract: Platelet Toll-Like Receptors in Essential Thrombocythemia downstream effector ERK1/2 was higher in patients at baseline and after incubation with Pam3CSK4, which may partly explain the enhanced TLR2 response. In conclusion, exacerbated response to TLR stimulation may promote platelet activation in ET, boosting platelet/leukocyte/endothelial interactions and secretion of inflammatory mediators, overall reinforcing the thromboinflammatory state. These findings highlight the role of platelets as inflammatory sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
(72 reference statements)
1
34
0
Order By: Relevance
“…Interestingly, no change in cell-surface expression of platelet-TLR2 was observed in septic patients, compared with both healthy and non-infectious controls within the intensive care unit [ 81 ] and this is despite infection inducing a similar magnitude of acute inflammatory response as that seen in ACS. Similarly, compared to healthy controls, no augmentation in platelet-TLR2 expression was seen in patients with essential thrombocythemia, a clinical condition associated with sustained thrombocytosis and thrombo-inflammation [ 82 ]. Platelet-TLR2 seems to be regulated variably during inflammation and seems likely to be important for the inflammatory response to cardiovascular pathology.…”
Section: An Update On Platelet-tlr Expression and Tlr-mediated Plamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, no change in cell-surface expression of platelet-TLR2 was observed in septic patients, compared with both healthy and non-infectious controls within the intensive care unit [ 81 ] and this is despite infection inducing a similar magnitude of acute inflammatory response as that seen in ACS. Similarly, compared to healthy controls, no augmentation in platelet-TLR2 expression was seen in patients with essential thrombocythemia, a clinical condition associated with sustained thrombocytosis and thrombo-inflammation [ 82 ]. Platelet-TLR2 seems to be regulated variably during inflammation and seems likely to be important for the inflammatory response to cardiovascular pathology.…”
Section: An Update On Platelet-tlr Expression and Tlr-mediated Plamentioning
confidence: 99%
“…Within the AF cohort, the greater time spent in AF (persistent vs. paroxysmal) was associated with an increase in platelet-TLR4 expression [ 80 ]. In contrast, no modulation of platelet-TLR4 expression is seen in patients with Essential Thrombocythemia, compared to healthy controls [ 82 ]. However, the culmination of these results suggests that platelet-TLR4 is actively upregulated during most clinical forms of infectious and injurious inflammation.…”
Section: An Update On Platelet-tlr Expression and Tlr-mediated Plamentioning
confidence: 99%
“…In the last decade, there has been increasing evidence that platelets do much more than just maintain hemostasis and thrombosis. Many studies demonstrated their contribution to immunity and a pivotal role in developing inflammation, infections, and cancer [ 26 , 27 , 28 , 29 , 30 , 31 ]. Circulating platelets function as guardians sensing pathogens by a set of pattern recognition receptors (PRRs), including TLR, nod-like receptors (NLR), and C-type lectin receptors (CLR).…”
Section: Platelets Biology and Functionsmentioning
confidence: 99%
“…Gangaraju et al conducted unbiased RNA sequencing and found differential expression of several thrombotic, inflammatory, and HIF-regulated genes in granulocytes and platelets of PV patients, especially in patients with a history of thrombosis [116]. Marín Oyarzún et al recently highlighted an additional inflammation/hypercoagulation cycle by demonstrating that hyperactive toll-like receptor (TLR) responses on platelet are characteristic in patients with ET and promote platelet activation, platelet interaction with leukocytes and the endothelium and secretion of inflammatory mediators [117]. In recent years the concept of 'thrombo-inflammation' was conceptualized to express the intimate cross-talk and mutual perpetuating effects of inflammation and thrombosis one upon the other [118].…”
Section: Thrombo-inflammation and Clonal Hematopoiesismentioning
confidence: 99%